Millets-The Nutritious Forgotten Crops (Journal of Pharmaceutical Negative Results, 2023)
Millets are used both as food and fodder. Various studies show that consumption of millets has reduced with time. Millets are healthy and nutritious for human consumption. In the current situation when health issues and diseases like obesity, diabetes and cardiovascular are high, the decrease in production and consumption of millets is not a good sign. If the demand for any commodity decreases, eventually its production reduces. Millets are climate resistance crop, suitable tool against fight with climate change and can easily undertake the climate and abiotic stress. They are rightly called as the crop of future as it also provides the additional food security. The people who are aware of the millets benefits purchase millets at high cost.  Present paper reviews the benefits of millets and reviews the reasons behind low production-consumption of millet in Indian scenario.